Fuel Minimizing Control for Constrained Relative Satellite Orbits - Gao, X.; Teo, Kok Lay; Sun, Y.; Duan, G. (WATAM Press, 2011)
In this paper, we study the fuel minimization problem of hovering satellite subject to a practical constraint on the trajectory of the deputy satellite. It is first shown that the constraint condition can be expressed equivalently as maximum flight time inequalities. On this basis, a cost function relating to the fuel burn is formulated. A numerical procedure is developed and an illustrative example is solved.